Analysis and Evaluation of Internal Control on Accounting Information System of Cash Receipt and Cash Payment at Unit Simpan Pinjam, KPN Politeknik Negeri Bali Based on COSO - N P T R Arisanthi; I K Parnata; I M Suarta (Jurusan Akuntansi Politeknik Negeri Bali, 2018)
The research aims to analyst and evaluate the internal control in accounting information systems of cash receipt and cash payment which applied at Unit Simpan Pinjam Koperasi Pegawai Negeri (KPN) Politeknik Negeri Bali (PNB). The evalution of this reseach is expected to increase th e internal control in accounting information system of cash receipt and cash payment and decrease risks of fraud, irregularity, and robbing of assets at KPN PNB.The kind of this research is case study, which the data were obtained by interview, observation, and documentation. Analyst technique was used in this research is descriptive and comparative which means that the realization of internal control at unit simpan pinjam KPN PNB was compared with the theory of internal control based on COSO. The result of this research showed that Unit Simpan Pinjam KPN PNB has four kind of cash receipt activities and four kind of cash payment activities. Those activities are general savings, be spaced savings, fixed deposit, and loan/credit. The result of internal control evaluation at unit simpan pinjam showed that there are two from five components of internal control based on COSO’s theory were same with realization of internal control in unit simpan pinjam. Those are control environment’s components and information and communication’s components. The other components such as risk evalution, control activities, and monitoring’s components were not matched between theory and realization.